2016
DOI: 10.1111/head.12827
|View full text |Cite
|
Sign up to set email alerts
|

The borderland of migraine and epilepsy in children

Abstract: Recent advances examining the migraine-epilepsy spectrum show clinicopathological similarities between the two disorders in children. Epidemiology demonstrates reciprocally increased incidences of epilepsy in migraineurs and of migraines in children with epilepsy, however, prospective longitudinal in children are currently lacking. Clinically, the two disorders show similarity in preictal, ictal, and postictal phenomena, with close temporal association of the two conditions described by the controversial term … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 65 publications
0
23
0
1
Order By: Relevance
“…Evaluation of migraine comorbidities, in particular, should be regarded as a pivotal part of the stratification process. It is well established, for example, that adults and children with migraine may have increased susceptibility to seizures (Rajapakse and Buchhalter, 2016 ). Identifying this potential comorbidity may allow efforts to dissect the genetic basis of the condition to be targeted toward specific sets of genes that may have a role in both migraine and epilepsy pathophysiology, such as the ion channels enhancing excitatory neurotransmitter release (i.e., Ca v 2.1) or dendrite neuronal excitability and firing (Na v 1.1), and their molecular interactors.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of migraine comorbidities, in particular, should be regarded as a pivotal part of the stratification process. It is well established, for example, that adults and children with migraine may have increased susceptibility to seizures (Rajapakse and Buchhalter, 2016 ). Identifying this potential comorbidity may allow efforts to dissect the genetic basis of the condition to be targeted toward specific sets of genes that may have a role in both migraine and epilepsy pathophysiology, such as the ion channels enhancing excitatory neurotransmitter release (i.e., Ca v 2.1) or dendrite neuronal excitability and firing (Na v 1.1), and their molecular interactors.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, the early reports on the connection of headache and epilepsy were based on the clinical observation of pediatric patients who experienced recurrent episodes of ‘intermediate’ in type between migraine and epilepsy. 6 , 38 In practice, it is often difficult to clinically distinguish migraine from epilepsy, and this effort is complicated in children because they are frequently not good at describe their symptoms and the attacks of both migraine and epilepsy are characterized by abrupt, paroxysmal changes in mood and behavior, sometimes consciousness and may be accompanied by changes in visual, motor, sensory, or speech function. 7 , 39 Children are more likely to have autonomic symptoms both in headache and epilepsy attacks, and they can have isolated, long-lasting ictal autonomic manifestations, while ictal autonomic manifestations (both in headache and epilepsy) in adults are usually associated, simultaneously or sequentially, with other motor or sensory ictal signs and symptoms both in headache and epilepsy attacks.…”
Section: Ictal Epileptic Headachementioning
confidence: 99%
“… 45 Compared to the short duration of visual hallucination of idiopathic childhood occipital epilepsy of Gastaut type, the visual phenomena caused by migraine with aura generally develop slowly within minutes with longer durations (up to 60 minutes by definition) 8 and tonic deviation of the eyes are also not seen in migraine. 6 Benign childhood occipital epilepsy of Panayiopoulos type typically presents between 3 and 5 years of age with rare prolonged and nocturnal seizures, marked autonomic features, followed by clonic motor symptoms. Although migraine is uncommon in this syndrome, poistictal migrainous headache is very common in these patients.…”
Section: Ictal Epileptic Headachementioning
confidence: 99%
See 1 more Smart Citation
“…Epilepsy and headache, frequently observed in comorbidity, share some clinical and pathophysiological characteristics that suggest a complex but not fully understood relationship. 5 It is commonly accepted that in adults with history of epilepsy, prevalence of headache is higher (35.5%) than in those without epileptic attacks (16.2%). 6 Similarly, a recent epidemiological study has shown migraine in 25% of epileptic children, more than in patients without epilepsy (3-23%).…”
mentioning
confidence: 99%